Assessing a financial incentive for reducing length of stay of psychiatric inpatients: Implications for financing psychiatric services (Swiss Medical Weekly, 2014)
QUESTIONS UNDER STUDY: Restricted government budgets are forcing countries to implement more efficient health measures. Unlike in somatic medicine, the process of evaluating payment systems in psychiatry in Switzerland is ongoing. A pilot approach in one psychiatric hospital, here called “new remuneration system (NRS)”, was introduced to better control length of stay (LOS) by combining a lump sum with degressive daily rates. This is a first evaluation of the NRS in terms of a reduction of the LOS, and the prevention of early readmissions by analysing meaningful outcome categories. METHODS: The total sample consisted of N = 66,626 psychiatric inpatient episodes and a subsample of N = 60,847. Data were collected from the hospital using the NRS and three comparison hospitals in the Canton of Zurich. The observation period covered 2005 to 2011, the years before and after the implementation of the NRS in 2009. To examine the outcome categories, general logistic models were used. RESULTS: The median LOS at all four hospitals was 21 days (IQR: 46–8). In the NRS-hospital, there was a significantly higher proportion of 6 to10-day stays after 2009, indicating an influence of the lumpsum measure. At the same time, data revealed a somewhat lower proportion of readmissions within 30 days in the NRS-hospital. In general, effect sizes were small. CONCLUSIONS: Within the observation period of three years since 2009, the NRS had a small influence on LOS and early readmissions. The stability of effects needs to be monitored. More sophisticated modellings of the NRS might lead to further insights.